Self-Control, Moral Disengagement, and Cyber-Aggression in Adolescents: The Mediating Roles of Advantageous Comparison and Distortion of Consequences - Muhammad Nafiis Ilhami; Miftahun Najah (Journal of Educational, Health and Community Psychology, 2026)
The increasing intensity of social media use among adolescents has heightened the risk of cyber-aggressive behavior. Adolescents in the transitional stage of development are particularly vulnerable to the influence of the digital environment, especially when it is not balanced by adequate self-control and moral standards. This study aims to examine the relationships between self-control and moral disengagement with cyber-aggression among adolescent social media users, and to test the mediating roles of two mechanisms—advantageous comparison and distortion of consequences—in these relationships. This study employed a quantitative correlational design. A total of 204 adolescents aged 18–22 years completed the Cyber-Aggression Typology Questionnaire (CATQ), a self-control scale, and a moral disengagement scale. Data were analyzed using linear regression and mediation analysis with the assistance of JAMOVI and JASP software. The results indicated that self-control was negatively and significantly associated with cyber-aggression, whereas moral disengagement was positively and significantly associated with cyber-aggression. Furthermore, the dimensions of advantageous comparison and distortion of consequences were found to mediate the relationship between self-control and cyber-aggression. These findings suggest that lower levels of self-control and higher levels of moral disengagement increase adolescents’ tendency to engage in cyber-aggression. Therefore, strengthening self-control and enhancing moral awareness are important aspects of preventing cyber-aggressive behavior among adolescents.